Rice iron storage protein ferritin 2 (OsFER2) positively regulates ferroptotic cell death and defense responses against Magnaporthe oryzae - Nguyen, Nam Khoa; Wang, Juan; Liu, Dongping; Hwang, Byung Kook; Jwa, Nam-Soo (Frontiers in Plant Science, 2022)
Ferritin is a ubiquitous iron storage protein that regulates iron homeostasis and oxidative stress in plants. Iron plays an important role in ferroptotic cell death response of rice (Oryza sativa) to Magnaporthe oryzae infection. Here, we report that rice ferritin 2, OsFER2, is required for iron- and reactive oxygen species (ROS)-dependent ferroptotic cell death and defense response against the avirulent M. oryzae INA168. The full-length ferritin OsFER2 and its transit peptide were localized to the chloroplast, the most Fe-rich organelle for photosynthesis. This suggests that the transit peptide acts as a signal peptide for the rice ferritin OsFER2 to move into chloroplasts. OsFER2 expression is involved in rice resistance to M. oryzae infection. OsFER2 knock-out in wild-type rice HY did not induce ROS and ferric ion (Fe3+) accumulation, lipid peroxidation and hypersensitive response (HR) cell death, and also downregulated the defense-related genes OsPAL1, OsPR1-b, OsRbohB, OsNADP-ME2-3, OsMEK2 and OsMPK1, and vacuolar membrane transporter OsVIT2 expression. OsFER2 complementation in ΔOsfer2 knock-out mutants restored ROS and iron accumulation and HR cell death phenotypes during infection. The iron chelator deferoxamine, the lipid-ROS scavenger ferrostatin-1, the actin microfilament polymerization inhibitor cytochalasin E and the redox inhibitor diphenyleneiodonium suppressed ROS and iron accumulation and HR cell death in rice leaf sheaths. However, the small-molecule inducer erastin did not trigger iron-dependent ROS accumulation and HR cell death induction in ΔOsfer2 mutants. These combined results suggest that OsFER2 expression positively regulates iron- and ROS-dependent ferroptotic cell death and defense response in rice–M. oryzae interactions.